THE IMPORTANCE OF MULTISLICE COMPUTED TOMOGRAPHY IN THE DIAGNOSIS OF CONGENITAL HEART DEFECTS IN CHILDREN (Herald of the National Children's Medical Center, 2025)
Congenital heart defects (CHDs) are among the leading causes of mortality in early childhood. Modern clinical cardiology demands high precision in assessing the morphometric parameters and anatomical features of the defect. Among the various imaging techniques, multislice computed tomography (MSCT) holds a prominent position due to its ability to provide simultaneous and detailed information about the morphological and functional state of the heart and vessels, which is critically important for planning surgical correction.
Keywords: MSCT; congenital heart defects (CHD); Tetralogy of Fallot; pulmonary artery; imaging; surgical planning